Patterns of physical activity in hunter-gatherer children compared with US and UK children - Luke Kretschmer; Mark Dyble; Nikhil Chaudhary; David Bann; Gul Deniz Salali (Scientific Reports)
Abstract Contemporary hunter-gatherers are highly active, but little is known about physical activity levels in hunter-gatherer children. We analysed 150 days of accelerometer data from 51 BaYaka hunter-gatherer children (aged 3–18) in the Republic of Congo, comparing it with British and American children using samples from Millennium Cohort Study (MCS) and National Health and Nutrition Examination Survey (NHANES). BaYaka children were highly active, engaging in over 3 h of moderate-to-vigorous physical activity (MVPA) daily, surpassing British adolescents by over 70 min. Unlike US children, whose activity diminished with age, BaYaka children’s activity levels increased, irrespective of gender. This trend suggests that formal education may suppress activity among American children, a pattern not seen in the BaYaka community. Reflecting their foraging lifestyle, activity patterns varied within and between days in BaYaka children, a contrast to the more uniform daily activity observed in American children. Furthermore, our data challenges the concept of ‘teenage chronotypes’ prevalent in post-industrial societies, with adolescent BaYaka maintaining shorter sleep phases and later bedtimes, synchronized with sunrise. These findings highlight the impact of a foraging upbringing on children’s activity levels, providing a benchmark for understanding childhood physical activity and wellbeing.